(Epi)genetic and clinical characteristics in 84 patients with pseudohypoparathyroidism type 1B - Urakawa, Tatsuki; Sano, Shinichiro; Kawashima, Sayaka; Nakamura, Akie; Shima, Hirohito; Ohta, Motoki; Yamada, Yuki; Nishida, Ai; Narusawa, Hiromune; Ohtsu, Yoshiaki; Matsubara, Keiko; Dateki, Sumito; et al. (European journal of endocrinology, 2023)
Pseudohypoparathyroidism type 1B (PHP1B) caused by methylation defects of differentially methylated regions (DMRs) on the GNAS locus can be categorized into groups according to etiologies and methylation defect patterns of the DMRs. The aim of this study was to clarify the clinical characteristics of each group. Comprehensive molecular analyses consisting of methylation, copy number, and microsatellite analyses. Eighty-four patients with PHP1B were included in this study. We classified them into 5 groups, namely, autosomal dominant inheritance-PHP1B (Group 1, G1), sporadic-PHP1B (G2), and atypical-PHP1B (G3-G5), based on the methylation defect patterns in 4 DMRs on the GNAS locus and etiologies and evaluated the clinical findings in each group and compared them among the groups. G2 had the youngest age and the highest serum intact parathyroid hormone levels among the 5 groups at the time of diagnosis. The most common symptoms at the time of diagnosis were tetany in G1, and seizures or loss of consciousness in G2. Albright's hereditary osteodystrophy and PHP-suggestive features were most frequently observed in the G2 proband. Nine patients had neurodevelopmental disorders (NDs) consisting of mild to borderline intellectual disability and/or developmental delay. There were no significant correlations between the average methylation ratios of 7 CpG sites in the GNAS-A/B:TSS-DMR and hormonal and biochemical findings. This study revealed the differences in some clinical characteristics, particularly clinical features, and ages at the time of diagnosis between G2 and other groups and detailed NDs observed in some patients with PHP1B.